How do Experts Forecast Sovereign Spreads? - Cimadomo, Jacopo; Claeys, Peter; Poplawski Ribeiro, Marcos (Washington, D.C. : International Monetary Fund, 2016)
This paper assesses how forecasting experts form their expectations about future government bond spreads. Using monthly survey forecasts for France, Italy and the United Kingdom between January 1993 and October 2014, we test whether respondents consider the expected evolution of the fiscal balance-and other economic fundamentals-to be significant drivers of the expected bond yield differential over a benchmark German 10-year bond. Our main result is that a projected improvement of the fiscal outlook significantly reduces expected sovereign spreads. This suggests that credible fiscal plans affect market experts' expectations and reduce the pressure on sovereign bond markets. In addition, we show that expected fundamentals generally play a more important role in explaining forecasted spreads compared to realized spreads.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet